'Equal play, equal pay': moral grounds for equal pay in football. Issue 3 (2nd September 2019) - Archer, Alfred; Prange, Martine
ABSTRACT: In this paper, we investigate three different ways of defending the claim that national football associations ought to pay their men's and women's football teams the same amount. First, we consider an argument that appeals to the principle of equal pay for equal work. We argue that this 'labor rights' argument provides a good reason for some national football associations to pay their men's and women's teams the same amount but that these are the exception rather than the rule. Next, we consider an alternative argument, which appeals to the 'expressive power' of paying women's football teams the same as men's. We argue that this argument can be applied more generally than the first argument and gives a good reason for many football associations to pay their men's and women's teams equally. However, this argument struggles to show that associations have a moral obligation to pay their men's and women's teams the same. We finish by considering the 'argument from historical injustice'. We argue that this argument provides plausible grounds for thinking that many associations not only have moral reasons to pay their men's and women's teams equally, but that they also have a moral obligation and a political responsibility to do so.